Robust stability analysis of LCL filter based synchronverter under different grid conditions - Rosso, Roberto; Cassoli, Jair; Buticchi, Giampaolo; Engelken, Soenke; Liserre, Marco (Institute of Electrical and Electronics Engineers, 2018)
Synchronverters have gained interest due to their capability of emulating synchronous machines (SMs), offering self-synchronization to the grid. Despite the simplicity of the control structure, the adoption of an LCL-filter makes the overall model complex again, posing questions regarding the tuning of the synchronverter and its robustness. The multi-inputs multi-outputs (MIMO) formulation of the problem requires multivariable analysis. In this paper, the effects of control parameter and grid conditions on the stability of the system are investigated by means of structured singular values (SSV or μ-analysis). A step-by-step design procedure for the control is introduced based on a linearized smallsignal model of the system. Then the design repercussions on the stability performance are evaluated through the performed robustness analysis. The developed linearized model is validated against timedomain simulations and laboratory experiments. These have been carried out using a power hardwarein- the-loop (PHIL) test bench, which allows to test the synchronverter under different grid conditions. As a conclusion the paper offers a simple guide to tune synchronverters but also a theoretical solid framework to assess the robustness of the adopted design.